STRUKTUR KOMUNITAS GASTROPODA PADA KOMUNITAS MANGROVE DI PANTAI AMAL LAMA KOTA TARAKAN - Dori Rachmawani (Fakultas Perikanan Dan Ilmu Kelautan Universitas Borneo Tarakan, 2010)
The study of structure communities gastropoda was since at communities mangrove in OldAmalBeachon November 2009. Taking sample do by using method transek quadrate. The analysis of data was density, abundance, and frequency presence use formula krebs (1978) and Index unity, Index dominansi and Suitability use formula odum (1994). The result of the research was show kind gastrophoda meet consist of 5 species from superfamily buccinacea, Family melongenidae, Genus melongena schumacher, With a few species are melongena funnel, Melongena patula, Pugilina morio, Pugilina sp, Melongena sp. Index of unity about 0,6689, Index dominansi about 0,2264 and Index suitability about 0,4156 Keyword: Gastropoda, Mangrove, Old Amal Beach